The West Wing : the American presidency as television drama - Rollins, Peter C.; O'Connor, John E. (Television series (Syracuse, N.Y.), 2003)
This work shows that while the series 'The West Wing' may be criticized as 'idealistic', its clever techniques of camera work, lighting, editing and mise en scene reflect America's best image of itself and entertain a loyal audience that wants to believe in the nobility of the American Dream.